Ain't no man: Female masculinity in Android game Legend of the PHOENIX - Adelia, Silvy; Dirgantari, Alfi; Hirano, Shun; Wedawati, Mamik; Ridha, Firly; Koiri, Much (Faculty of Languages, Arts, and Culture Universitas Negeri Yogyakarta, 2024)
This study performs content analysis on an Android game titled Legend of the Phoenix. Legend of the Phoenix, commonly known as LoP, is an otome (girl) game released by Modo Game in 2020. Like most otome games, Legend of the Phoenix revolves around the journey of a young woman who is given a second chance at life after her first ends tragically. The player takes the role of this young woman and has to complete various missions and storylines in order to complete the game. This study aims to find messages about gender presented in the game by analyzing its visual and narrative content. It focuses on identifying female masculinity in the special recruitment group of Female General or Heroine. The game characters being analyzed are the four Generals in Legend of the Phoenix